Long-life aqueous organic redox flow batteries enabled by amidoxime-functionalized ion-selective polymer membranes - Ye,C; Tan,R; Wang,A; Chen,J; Comesaña,Gándara B; Breakwell,C; Alvarez-Fernandez,A; Fan,Z; Weng,J; Bezzu,CG; Guldin,S; Brandon,N; et al. (Angewandte Chemie International Edition, 2022)
Redox flow batteries (RFBs) based on aqueous organic electrolytes are a promising technology for safe and cost-effective large-scale electrical energy storage. Membrane separators are a key component in RFBs, allowing fast conduction of charge-carrier ions but minimizing the cross-over of redox-active species. Here, we report the molecular engineering of amidoxime-functionalized polymers of intrinsic microporosity (AO-PIMs) by tuning their polymer chain topology and pore architecture to optimize membrane ion transport selectivity. AO-PIM membranes are integrated with three emerging aqueous organic flow battery chemistries, and the synergetic integration of ion-selective membranes with molecular engineered organic molecules in neutral-pH electrolytes leads to significantly enhanced cycling stability.